Pengembangan Media Pembelajaraan Sosial Emosional (PSE) Berbentuk Doratoon pada Kelas V SD Negeri 27 Salafen Kabupaten Raja Ampat - Yubelina Oktofina Hay; Firman Firman; Dian Nitari Ribanor Sabarudin (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
SD Negeri 27 Salafen in Raja Ampat has not yet implemented varied video learning media. This study aims to develop a valid, practical, and effective Doratoon-based video learning media for use in the learning process. The research method used is Research and Development (R&D), adopting the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observation, interviews, documentation, and other data collection instruments. The subjects of this study were 24 students from grade V of SD Negeri 27 Raja Ampat. Based on the results, the development of Doratoon-based video learning media showed very positive results. Validation was conducted by two validators, namely a material expert and a media expert. The material expert’s validation resulted in an average percentage of 97%, while the media expert achieved an average percentage of 86%, both falling into the